Magnetic and Cytotoxicity Properties of La1−x Sr x MnO3(0 ≤ x ≤ 0.5) Nanoparticles Prepared by a Simple Thermal Hydro-Decomposition - Siri Sineenat; Mongkolkachit Charusporn; Daengsakul Sujittra; Thomas Chunpen; Thomas Ian; Amornkitbamrung Vittaya; Maensiri Santi (Nanoscale Research Letters, 2009)
Abstract This study reports the magnetic and cytotoxicity properties of magnetic nanoparticles of La1−x Sr x MnO3(LSMO) withx = 0, 0.1, 0.2, 0.3, 0.4, and 0.5 by a simple thermal decomposition method by using acetate salts of La, Sr, and Mn as starting materials in aqueous solution. To obtain the LSMO nanoparticles, thermal decomposition of the precursor was carried out at the temperatures of 600, 700, 800, and 900 °C for 6 h. The synthesized LSMO nanoparticles were characterized by XRD, FT-IR, TEM, and SEM. Structural characterization shows that the prepared particles consist of two phases of LaMnO3(LMO) and LSMO with crystallite sizes ranging from 20 nm to 87 nm. All the prepared samples have a perovskite structure with transformation from cubic to rhombohedral at thermal decomposition temperature higher than 900 °C in LSMO samples ofx ≤ 0.3. Basic magnetic characteristics such as saturated magnetization (M S) and coercive field (H C) were evaluated by vibrating sample magnetometry at room temperature (20 °C). The samples show paramagnetic behavior for all the samples withx = 0 or LMO, and a superparamagnetic behavior for the other samples havingM Svalues of ~20–47 emu/g and theH Cvalues of ~10–40 Oe, depending on the crystallite size and thermal decomposition temperature. Cytotoxicity of the synthesized LSMO nanoparticles was also evaluated with NIH 3T3 cells and the result shows that the synthesized nanoparticles were not toxic to the cells as determined from cell viability in response to the liquid extract of LSMO nanoparticles.